Saving Milly love, politics, and Parkinson's Disease - Kondracke, Morton (New York Public Affairs, 2001)
Kondracke chronicles his marriage, becoming a caregiver and an activist, and the realities of "disease politics".
"Marry Milly!" -- The Old Milly -- Invasion -- Heroine -- The New Mort -- Politics -- God's Work -- Losing Milly.
Includes index.
Keywords: Kondracke, Milly -- Health; Parkinson's disease -- Patients -- United States -- Biography